2015
DOI: 10.1016/j.neuroscience.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical and functional characterization of CRF neurons of the amygdala using a novel transgenic mouse model

Abstract: The corticotrophin releasing factor (CRF)-producing neurons of the amygdala have been implicated in behavioral and physiological responses associated with fear, anxiety, stress, food intake and reward. To overcome the difficulties in identifying CRF neurons within the amygdala, a novel transgenic mouse line, in which the humanized Renilla reniformis green fluorescent protein (hrGFP) is under the control of the CRF promoter (CRF-hrGFP mice), was developed. First, the CRF-hrGFP mouse model was validated and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 84 publications
2
22
0
4
Order By: Relevance
“…The viral expression was almost completely limited to the CeAmy with only a few scattered cells in the medial amygdala. This expression pattern matches the previously described pattern of CRF immunoreactivity in rats [43, 44] and mice [45]. We also performed antibody labeling.…”
Section: Resultssupporting
confidence: 86%
“…The viral expression was almost completely limited to the CeAmy with only a few scattered cells in the medial amygdala. This expression pattern matches the previously described pattern of CRF immunoreactivity in rats [43, 44] and mice [45]. We also performed antibody labeling.…”
Section: Resultssupporting
confidence: 86%
“…However, such behaviors are likely mediated by non-PVN CRF systems since the vast majority of PVN CRF neurons are hypophysiotropic (Wamsteeker Cusulin et al, 2013). In line with this possibility, it has been shown that some stress-related fear-modulating effects of ghrelin do not involve the HPA axis activity but rather the amygdala (Meyer et al, 2014), where CRF neurons are also present (De Francesco et al, 2015). Thus, future studies are required to understand the interplay between the neuronal circuits mediating the effects of ghrelin on stress-related behavioral and neuroendocrine responses.…”
Section: Discussionmentioning
confidence: 93%
“…First, exposure to both predator stress and EPM induced neuronal activation in the BNST, but not the central amygdala, and similar levels of neuronal activation were seen in both the high and low anxiety groups in the BNST after EPM exposure. CRF-positive neurons in the CEA project to regions such as the periaqueductal gray [18, 19] and have recently been demonstrated to be activated following acute social defeat stress [24]. Dual-labeled immunohistochemistry showed that rats which were exposed to butyric acid, ferret odor, or exposure to the EPM displayed no change in co-localization of CRF with c-Fos in any subdivision of the CEA compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated that the central amygdala does mediate unconditioned anxiety to the EPM [45]. In addition, CRF-containing neurons of the central amygdala displayed increased co-localization with c-Fos in a number of acute behavior paradigms including acute social defeat stress, a fasting/feeding paradigm, and lipopolysaccharide administration [24]. Furthermore, a previous study determined that the CEA mediates unconditioned anxiety in the EPM test through enkephalin-dependent mechanisms [46] which supported our own previous studies which demonstrated a role of opioids and the μ-opioid receptor in the CEA in mediating anxiety-related behaviors and the actions of anxiolytics in the EPM and defensive burying task [25, 4749].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation